Esophageal rupture complicated by acute pericarditis - Hakan Duman; Eftal Murat Bakırcı; Zakir Karadağ; Yavuz Uğurlu (KARE Publishing, 2014)
Esophageal perforation is a serious condition with a high mortality rate. Delayed detection of esophageal perforation may result in devastating complications such as mediastinitis and pericarditis. Esophageal perforation is rarely due to aspiration of foreign bodies. Here we report the case of a 59-year-old male patient with complicated esophageal perforation due to ingestion of a chicken bone, whose first signs are considered to be acute non-specific pericarditis.